2021
DOI: 10.1002/vzj2.20172
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the joint use of GPR and ERT on mapping shallow subsurface features of karst critical zone in southwest China

Abstract: The soils and underlying weathered carbonate rock in karstic regions play an important role in the infiltration, storage, and retention of water and nutrients. Because of significant heterogeneity of the karst, the use of individual geophysical techniques is often not sufficient for unambiguous assessment of the irregular distributions of soils and underlying fractures. In this study, ground penetrating radar (GPR) and electrical resistivity tomography (ERT) are jointly used with additional observations to del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The Atterberg limits and particle size distribution of the soil samples were determined following the Chinese National Standards (CNS) GB/T50123-2019 [47] (pp. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The bulk mineralogy and clay mineralogy of the rock samples were measured using an X-ray diffractometer following the methods described by Moore and Reynolds [48] (p. 378).…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Atterberg limits and particle size distribution of the soil samples were determined following the Chinese National Standards (CNS) GB/T50123-2019 [47] (pp. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The bulk mineralogy and clay mineralogy of the rock samples were measured using an X-ray diffractometer following the methods described by Moore and Reynolds [48] (p. 378).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Given the non-uniqueness of dataset interpretation, and the drawbacks of individual techniques in resolution and penetration depth, GPR and ERT have been jointly used for the investigation of subsurface features thanks to their complementarity [35][36][37][38][39][40][41][42][43]. Jongmans and Garambois [28] concluded that almost all the advantages of the geophysical method corresponded well to the disadvantages of the conventional geotechnical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…International scientific literature has reported many geophysical applications to areas at risk of subsidence [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This technique discriminates between developing sinkholes and mature sinkholes comprising resistive air-filled cavities. Reference [ 8 ] used ERT and GPR methods to map subsoil in karstic areas. They concluded that ERT is effective for detecting soil–rock interfaces and even irregular terrain and fracture structures, such as funnel-shaped dolines.…”
Section: Introductionmentioning
confidence: 99%
“…The depth of GPR also has certain limitations. In recent years, many case studies of GPR combined with the resistivity method have been reported, and the combination of the two methods and technologies has been proved to be an effective means for imaging and characterization of underground karst [5,6,7,8]. In this paper, GPR and ERT surveys are carried out simultaneously in the research area.…”
Section: Introductionmentioning
confidence: 99%